Mexican American religions: spirituality, activism, and culture - Espinosa, Gastón; García, Mario T. (Duke Univ. Press, 2008)
History and interpretations of Mexican American religions -- History and theory in the study of Mexican American religions / Gastón Espinosa -- Pious colonialism : assessing a church paradigm for Chicano identity / Anthony M. Stevens-Arroyo -- Mexican American mystics and prophets -- Sacred order, sacred space : Reies López Tijerina and the Valle de Paz community / Rudy V. Busto -- Holy activist, secular saint : religion and the social activism of César Chávez / Stephen R. Lloyd-Moffett -- Religion and the Chicano movement : Católicos por la raza / Mario T. García -- Mexican American popular Catholicism -- Our Lady of Guadalupe and the politics of cultural interpretation / Socorro Castañeda-Liles -- Voces de Fe : Mexican American altaristas in Texas / Kay Turner -- Los pastores and the gendered politics of location / Richard R. Flores -- Mexican American religions and literature -- The religious vision of Gloria Anzaldúa : Borderlands/La frontera as a shamanic space / Davíd Carrasco and Roberto Lint Sagarena -- Voice and vision in Chicana religious practice : the literary re-elaborations of Mary Helen Ponce, Denise Chávez, and Sandra Cisneros / Ellen McCracken -- Mexican American religions and healing -- Brown Moses : Francisco Olazábal and Mexican American Pentecostal healing in the Borderlands / Gastón Espinosa -- Borderlands bodies and souls : Mexican religious healing practices in East L.A. / Luis D. León -- Mexican American religions and pop culture -- Luis Valdez's La pastorela: "the shepherds' play" : tradition, hybridity, and transformation / María Herrera-Sobek -- Hybrid spiritualities and Chicana altar-based art : the work of Amalia Mesa-Bains / Laura E. Pérez -- Mexican Madonna : Selena and the politics of cultural redemption / Gastón Espinosa -- Conclusion: Reflections on Mexican American religions and culture